PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VII DI SMP NEGERI 25 PEKANBARU - Hanifah, Nurul Fanny; Syahza, Almasdi; Haryana, Gani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the application of the Number Head Together (NHT) cooperative learning model to increase student learning activity in Class VII social studies subjects. This survey was conducted at SMP Negeri 25 Pekanbaru in the 2019/2020 school year. This research takes the form of experimental research. The population in this study was class VII with a total of 367 students from 9 classes, while the study group was 78 students. Sampling using class sampling technique. The research tool used was the observation sheet (teacher activity, student activity, student learning activity and documentation) for retrieving data using (pos test). Data analysis of student learning activity in social studies using another test shows that student learning activity after treatment with NHT with a mean value of 57% in Treatment I, 58% in Treatment II, and 62% in Treatment III, greater than class for treatment with NHT is 39%. Thus, it can be concluded that the NHT type cooperative learning model to increase the learning activity of students should be considered as one of the learning models used in the learning processKey Words: Model Number Head Together (NHT), Active Learning